Herringbone Microfluidic Probe for Multiplexed Affinity‐Capture of Prostate Circulating Tumor Cells. Issue 6 (19th April 2021) - Glia, Ayoub; Deliorman, Muhammedin; Sukumar, Pavithra; Janahi, Farhad K.; Samara, Bisan; Brimmo, Ayoola T.; Qasaimeh, Mohammad A.
Abstract: In this work, for first time, circulating tumor cells (CTCs) are captured on an open biofunctionalized substrate with multiplexing capability. This is achieved by developing a new microfluidic probe (MFP) integrated with radially staggered herringbone (HB) elements for microvortex generation. The new tool, named as herringbone microfluidic probe (HB‐MFP), is a channel‐less microfluidic system with physically separated bottom capture substrate and top fluidics delivery system. The concept allows for functionalizing the capture substrate with multiple biorecognition ligands (in this work, stripes of different capture antibodies) and scanning the fluidics delivery system across the substrate in a 2D printing‐like movement. Using the HB‐MFP, CTCs are efficiently captured from prostate cancer blood samples through their specific EpCAM, PSMA, and PSA antigens in a single run, with counts ranging from as low as 6 CTCs mL ‐1 (localized cancer patients) to as high as 280 CTCs mL ‐1 (metastatic cancer patients). In the process, CTC clusters with sizes of as high as 40–50 cells are also successfully captured. The results indicate that multiplex profiles of CTCs could reveal certain cellular phenotypes based on PSMA and PSA expression levels. The developed HB‐MFP is simple and robust to use, allows for high throughput sample processing, and provides seamless access to captured CTCs for further downstream characterization. Abstract : Channel‐less herringbone microfluidic probe (HB‐MFP) with independent bottom biofunctional substrate for multiplexed capture of single and cluster prostate circulating tumor cells (CTCs) from whole blood samples is presented here. The open‐space configuration allows the HB‐MFP to scan over the substrate functionalized with multiple stripes of capture antibodies, for cell capture in a 2D‐printing‐like approach.